The Valuation of Stock Options: Comment - Boness, A. James (Journal of Financial and Quantitative Analysis, 1968)
In a recent article in this journal, Harold Bierman, Jr. takes me to task for an alleged incompleteness and insufficiency of my “Elements of a Theory of Stock-Option Value.” The criticism consists of an insistence that option (call) values are relative to alternative long positions in common stock, rather than of “absolute” and independent value as options per se.